Eradicating Poverty in India by Sun using Dye Sensitized Photovoltaic Technology (Journal of Tropical Resources and Sustainable Science (JTRSS), 2016)
Almost all 1.6 billion people in developing countries have no access to electricity; approximately 85% of the people live in rural areas. Poor people and people in marginal areas, presently depend on natural resources such as wood, charcoal, dung etc. to provide energy for cooking and heating. By 2030, in this category is expected to rise from 2.4 to 2.6 billion people. The result will be greater local competition for traditional energy. So, the rural development can be achieved by promoting locally available renewable energy to meet the basic electricity needs. Decentralised production units are appropriate wherever locally renewable sources of energy are available. Efficient use of traditional and commercial fuels. The main focus of this paper is to present the energy management techniques and different applications of solar energy utilization for the rural people in India to eradicate the poverty in addition to this the role of youth, educationalists, researchers, scientists, politicians and bureaucrats etc. to eradicating poverty in the nation.
Keywords: PV system; poverty eradication; dye sensitized solar cell; renewable energy source; energy management